Science in East and West: Transformation and integration of the East German science system - Werner Meske (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 1994)
In the GDR, science was largely oriented on underpinning political objectives and in particular on promoting the economy. On the basis of a linear model of research and innovation processes, a specific hierarchically structured organizational and management structure for research was created and integrated into the overall centralist state management system. In the process of German unification, efficient nuclei of this research system were to be retained and integrated into a new science system for the whole of Germany on the West Germany model. Although the transfer of institutions from West to East has largely been completed, research in East Germany differs considerably from that in West Germany in both quantitative and structural respects. The decline and structural deformation of industrial research is a particular obstacle to resuscitating academy-industry relations, and displays the mark of 'peripheral development' in East Germany. – – In der DDR war die Wissenschaft weitgehend auf die Unterstützung der politischen Zielstellungen und insbesondere auf die Förderung der Wirtschaft orientiert gewesen. Ausgehend von einem linearen Modell von Forschungs- und Innovationsprozessen war eine spezifische hierarchisch gegliederte Organisations- und Leitungsstruktur der Forschung geschaffen und in das staatliche zentralistische Leitungssystem eingebunden worden. Im Prozeß der deutschen Vereinigung sollten leistungsfähige Kerne dieses Forschungssystems erhalten und in eine neue gesamtdeutsche Wissenschaft, die nach bundesdeutschem Muster gestaltet ist, integriert werden. Obwohl der Institutionentransfer von West nach Ost inzwischen weitgehend vollzogen worden ist, weist die Forschung in Ostdeutschland erhebliche quantitative und strukturelle Unterschiede zu der in Westdeutschland auf. Insbesondere der Niedergang und die struk-turelle Deformation der Industrieforschung behindern die Wiederbelebung von Akademie- Industrie-Beziehungen und lassen in Ostdeutschland Merkmale einer peripheren Ent-wicklung erkennen.
Keywords: 300; Forschung; Industrielle Forschung; Wissenschaft; Neue Bundesländer